Distribution and quantitation of skin iron in primary haemochromatosis: correlation with total body iron stores in patients undergoing phlebotomy - Pinheiro, Teresa (2014)
Measurement of the concentration of iron in the skin, if correlated with total body iron stores, may enable better informed decisions on when to initiate, change or stop therapy in hereditary heamochromatosis. Naïve haemochromatosis patients with iron overload and with C282Y and/or H63D HFE mutations were evaluated at the following time-points: disease diagnosis, end of the therapy programme, and 6 months after the end of therapy. The distribution and concentration of iron in the skin were assessed by quantitative nuclear microscopy methods, in parallel with serum and plasma iron concentration. Iron content in the liver was determined by nuclear magnetic resonance. Iron accumulated in the epidermis; its concentration increased from outer to inner layers, being maximal in the basal layer (7.33?±?0.98 µmol/g). At all 3 time-points, most of the iron was associated with the extracellular space. During the phlebotomy programme the iron content of the skin and the liver decreased by a factor of 2. These data suggest that measurements of iron concentration in the epidermis, which is a readily accessible tissue, reflect iron overload in the liver.